Sistem Informasi E-Catalogue Umroh Berbasis Web Untuk Tim Sales PT Khadijah Travel Indonesia - Muhammad Abdul Jabbar Al-Gifari; Farizi Ilham; Afisty Nayyara; Arief Wicaksono (CV. Shofanah Media Berkah, 2026)
PT. Khadijah Travel Indonesia is a company that provides travel services for performing umrah, offering various packages for those who wish to go. The sales team still relies on traditional methods as printed brochures and PDF files to distribute product information, which results in limited information sharing, difficulty in updating package data, and an inefficient marketing procces. This internship activity aims to design and develop a web-based E-Catalogue information system for umrah packagaes. This system will assist the sales team in sharing product information in a more effective and efficient manner. The system was developed using the waterfall model of the system development Life Cycle (SDLC), which includes stages such as analysis, design, implementation, and testing. Data was collected through observation, interviews, and literature review. The outcome of this activity is an E-Catalogue system featuring package data management, a digital catalogue layout, product search, and acces management for administrators and the sales team. This system is able to simplify product information sharing, accelerate data updates, and improve work efficiency in the field of marketing.